Competences of Engineers. Evidence from a Comparative Study for Russia and EU countries - Shmatko, Natalia (Foresight and STI Governance, 2012)
This paper assesses ​​knowledge and skill levels required for engineers in an ideal labor market. Understanding the demand and supply of engineers’ skills is important for modernization policies, and it is also important to know how to measure skill absorption by employees. Based on empirical research, the author evaluates the skill levels and absorption capacities of Russian engineers to measure what knowledge they can mobilize to resolve professional tasks. It constructs profiles of the different categories of engineering personnel. It compares demand and supply of engineering skills in Russia and EU countries in five categories: use of professional knowledge, individual performance, team work, managerial and communication skills. The analysis shows significant distinctions among compared countries. To summarize, the level of general and special competencies for Russian engineers is well below what is required by their workplace. The contrary can be said about their European counterparts, who have the required skills. Serious discrepancies between Russian and European engineers (favouring Europeans) are observed for organization and coordination skills, team work, effective use of time, ability to evaluate critically their own and others’ ideas, use the computer and the Internet for professional purposes. The availability of specialized engineering skills alone is insufficient in today’s job market: employers expect a more proactive approach by the engineers, including the promotion of the products. In view of various "distortions" in the training of engineers, not only in Russia but also in other countries, where the patterns of portfolios in the labour market do not match the demand for them, the possession of social skills is of particular value.